PROSES GRADUASI INTENSITAS TRANSISI DENGAN GENERALIZED LINEAR MODEL PADA MODEL MULTI STATUS DAN APLIKASINYA PADA PERHITUNGAN PREMI ASURANSI KESEHATAN RAWAT JALAN - , ISTIQOMAH, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One important assumption in pricing health insurance products is the probability of the individual suffering from a disease or illness. To determine the probabilities can be used multi-model status. There are several approaches in solving the multistate model, one is transition intensity approach. Transition probabilities from a state to another formed from the transition intensities. The transition intensities is not known their exact value, therefore it needs to be estimated. One of method is maximum likelihood approach, which would produce crude intensities. Then the next step is graduate the crude intensities in order to produce smooth transition intensities. Graduation formed by the Generalized Linear Models (GLM). The smooth intensities used to calculate transition probabilities associated with differential equations Kolmogorov Backward and Forward. These result used as one of the assumptions in determining outpatient health insurance premiums.